Correlations between Antioxidant Activity and Alkaloids and Phenols of Maca (Lepidium meyenii) - Jin Gan; Ying Feng; Zhao He; Xian Li; Hong Zhang (Journal of Food Quality)
The antioxidant capacity of maca has been considered to be the basis for other bioactivities, and revealing the active antioxidant compounds would help to elucidate a variety of bioactive compounds. In this study, the correlation between the antioxidant activity of maca and secondary metabolites, including ferric reducing antioxidant potential (FRAP), hydroxyl radical scavenging ability (HRSA), lipid peroxidation inhibition ability (LPIA), total phenolic contents (TPCs), total alkaloid contents (TACs), and total sterol contents (TSCs), was investigated by measuring. Chloroform was selected to be an efficient extraction solvent for antioxidant compounds in maca by polarity fractions test. The results showed that TPC exhibited significant linear correlations (P<0.05) to FRAP and LPIA, while TAC had significant linear correlations (P<0.05) to FRAP, HRSA, and LPIA. These results suggested that alkaloids and phenols were the most important substances for the antioxidation of maca, of which the antioxidant effect of alkaloids seemed to be higher than that of phenols.